Broad-spectrum antiviral that interferes with de novo pyrimidine biosynthesis - Hoffmann, Hans-Heinrich; Kunz, Andrea; Simon, Viviana A; Palese, Peter; Shaw, Megan L (Proceedings of the National Academy of Sciences - PNAS, 2011)
Compound A3 was identified in a high-throughput screen for inhibitors of influenza virus replication. It displays broad-spectrum antiviral activity, and at noncytotoxic concentrations it is shown to inhibit the replication of negative-sense RNA viruses (influenza viruses A and B, Newcastle disease virus, and vesicular stomatitis virus), positive-sense RNA viruses (Sindbis virus, hepatitis C virus, West Nile virus, and dengue virus), DNA viruses (vaccinia virus and human adenovirus), and retroviruses (HIV). In contrast to mammalian cells, inhibition of viral replication by A3 is absent in chicken cells, which suggests species-specific activity of A3. Correspondingly, the antiviral activity of A3 can be linked to a cellular protein, dihydroorotate dehydrogenase (DHODH), which is an enzyme in the de novo pyrimidine biosynthesis pathway. Viral replication of both RNA and DNA viruses can be restored in the presence of excess uracil, which promotes pyrimidine salvage, or excess orotic acid, which is the product of DHODH in the de novo pyrimidine biosynthesis pathway. Based on these findings, it is proposed that A3 acts by depleting pyrimidine pools, which are crucial for efficient virus replication.